Numerical investigation of low velocity out of plane impact behavior of Kevlar composites. (2019) - Manigandan, S.; Gnana Nandita, P.; Krishna Teja, D.; Gunasekar, D.; Nithya, S.; Devipriya, J.
Abstract: Strength of composite materials is increased with the help of enormous advancement in material science technology. However the strength of materials under transverse loading has been complicated since the prediction of internal delamination damage of the fibre is difficult. This usually occurs when the laminate encountered low velocity impact condition like bird strike in aircraft. This paper focus on evaluation of Kevlar 49 and 149 crossply laminate (0/90/0/90)s which is subjected to out of plane impact computationally. The impact velocity is 5m/s and the mass of the impactor is 0.5kg. A numerical analysis is carried out on specimen using finite element analysis approach. The FEA results are taken and evaluated with the failure modes to find optimized failure modes and threshold impact damage.